Congenital Thyrotoxicosis with Congenital Glaucoma: A Case Report - Bari, MI; Hoque, ME; Alam, T; Choudhury, KM (TAJ: Journal of Teachers Association, 2009)
A case of preterm neonate with congenital thyrotoxicosis associated with congenital glaucoma is reported. Her mother had undiagnosed thyrotoxicosis. The diagnosis of thyrotoxicosis in the neonate was confirmed by an elevated serum tri-iodothyronine (T3) level of 8.09 nmol/L, thyroxin (T4) level of 3.09 nmol and thyroid stimulating hormone (TSH) level 0.16mu/L. Congenital glaucoma was confirmed by increased intraocular pressure (IOP) which was 42.1 mmHg in right eye and 38.2 mm Hg in left eye. Corneal diameter was increased which was 13 mm in both eyes. Corneal oedema and Haab striae were also present. Probably, this is the first case of congenital thyrotoxicosis associated with congenital glaucoma reported in Bangladesh. doi: 10.3329/taj.v20i1.3094 TAJ 2007; 20(1): 64-66